Leitura e escrita por meio do jogo de RPG Robinson Crusoé: uma proposta de multiletramentos - Morais, Rozane Mendonça Cardoso de (2019)
This dissertation is the result of a research centered on the elaboration and application of a reading and writing proposal, with emphasis on the discursive genre, through RPG (Role-Playing Game) and the literary work Robinson Crusoe, with the intention to contribute to the development of students' discursive competence and to multilevel practices in school. The specific objectives of the study are: a) to investigate students' knowledge about RPG games and about contact with literary texts, especially the genre story; b) to present RPG games, on a board and online, as a productive hypergene for the development of the practice of reading and writing in school, especially the genre tale, to explore them in their specificities by reading and analyzing these games and participation in them; c) promote the reading and analysis of stories in the classroom, explore the specificities and produce copies of this genre; d) to develop digital literacy and games through literary literacy and multiliteracy practices; e) analyze discursive representations of the world and identifications constructed in and from the texts read and the texts produced by the students; f) elaborate and make available on the website supplementary notebook with the proposal presented, in order to subsidize the work of other teachers with reading and writing through RPG games. In order to reach the proposed objectives, the research is based on studies and official documents about the teaching of the Portuguese Language in Brazil, studies on discursive genres, digital genres and hypergenerics, such as RPG, storytelling, multiliteracies, pedagogy of the multiliteracies, literary literacy, and theoretical and methodological assumptions of Critical Discourse Analysis (CDA). The methodology adopted for conducting the research is qualitative and the procedure is action research. For the generation and collection of data we use questionnaires, recordings, field diary, oral and written reports, portfolio, production of texts of different genres. The results of the analysis of this proposal, applied in a 7th grade class of a public school in the city of Brazlândia, Federal District, reveal that, through a teaching focused on the social practices in which students participate, it considers and values knowledge of the world they bring with them, the various semiosys, multiliteracies and recognizes the work with the texts as materialization of speeches, we can contribute to a more meaningful reading and writing teaching. In addition, the didactic strategy presented in this dissertation contributes, from the reading and writing practices elaborated, applied and analyzed, to a teaching that improves students' discursive competence and forms citizens who will participate critically in diverse social practices.